FRUIT QUALITY AND YIELD OF DATE PALM (Phoenix dactylifera L.) AS AFFECTED BY STRAND THINNING - M. A. Bashir; M. Ahmad; F. Altaf; K. Shabir (Journal of Animal and Plant Sciences, 2014)
Kur cultivar of date palm is a high yielder but it has small fruit size. Small fruit size of date palm is not popular among the date growers. An experiment was conducted during 2008-10 on plants of date palms (Phoenix dactylifera L.) cv. "Kur" at Horticultural Research Station, Bahawalpur (Pakistan) to improve quality fruit parameters of this cultivar by strand thinning. The plants were of 20-year-old, uniform in size, growth and vigour which were kept under normal schedule of cultural practices. Hand pollination was carried outduring the 2nd week of March in three seasons using the same pollen source. Four strand thinning treatments i.e., T1=control (without thinning), removal of strands 10% (T2), 25% (T3) and 50% (T4) were applied by removing the strands randomly from total strands per bunch after 5 weeks from pollination. The experiment was laid out according to RCBD with 3 replications. The leaf bunch ratio was maintained at 5:1. Fruit dimension, fruit weight, TSS% and yield per plant improved by all levels of strand thinning as compared to control. Maximum fruit dimension (length x diameter=3.88 x 2.6 cm), fruit weight (13.7 g), TSS (30.33%) and yield (107 kg/palm) along with minimum stone pulp ratio (10.64%) and fruit drop (17.34%) were recorded by 50% strand thinning, followed by the treatment where 25% strands were removed. Positive correlation existed between fruit yield and fruit weight at 50% strand thinning.
Keywords: Phoenix dactylifera L.; date palm; strand thinning; yield; fruit quality